2014
DOI: 10.1002/wps.20088
|View full text |Cite
|
Sign up to set email alerts
|

A newly identified group of adolescents at “invisible” risk for psychopathology and suicidal behavior: findings from the SEYLE study

Abstract: This study explored the prevalence of risk behaviors (excessive alcohol use, illegal drug use, heavy smoking, reduced sleep, overweight, underweight, sedentary behavior, high use of Internet/TV/videogames for reasons not related to school or work, and truancy), and their association with psychopathology and self-destructive behaviors, in a sample of 12,395 adolescents recruited in randomly selected schools across 11 European countries. Latent class analysis identified three groups of adolescents: a low-risk gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
99
1
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 55 publications
14
99
1
12
Order By: Relevance
“…To this end, we examined the internal structure, tested the measurement invariance across countries, and estimated the internal consistency of the SDQ scores. Knowledge of the SDQ psychometric properties is relevant to use it as a screening tool in an age group at particular risk of developing emotional and behavioural symptoms and disorders [1,[4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we examined the internal structure, tested the measurement invariance across countries, and estimated the internal consistency of the SDQ scores. Knowledge of the SDQ psychometric properties is relevant to use it as a screening tool in an age group at particular risk of developing emotional and behavioural symptoms and disorders [1,[4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is worth noting that measurement invariance was reached after factor loadings and threshold of items were freed (1,2,6,7,15,16,17,20,21,22, and 23), in the five-factor model with correlated errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-centre Saving and Empowering Young Lives in Europe (SEYLE) study reported that 5.8% of participants met criteria for an anxiety disorder, 10.5% met criteria for depressive disorder [15], while 32.3% reported suicidal thoughts [16]. In this study we examined physical activity and its associations with mental health indicators in the SEYLE sample.…”
Section: Introductionmentioning
confidence: 99%
“…Otra cuestión importante es la referente al consumo de sustancias que nos indica que más del 90% de los menores del Grupo Trampolín consume algún tipo de droga de forma habitual, siendo el alcohol y el cannabis las sustancias más consumidas. Son numerosas las investigaciones que relacionan los trastornos graves del comportamiento con conductas de riesgo como el consumo de drogas (Bernal y González-Tascón, 2009;Carli et al, 2014;Gutiérrez et al, 2008;Howell, 2003;Plattner et al, 2012;Quinsey, Skilling, Lalumière y Craig, 2004); estos estudios coinciden con los resultados hallados en Trampolín sobre este aspecto concreto, por lo que se puede afirmar que los menores del programa tienen como característica común el ser consumidores habituales tanto de sustancias socialmente aceptadas (alcohol y tabaco) como de otras consideradas ilegales. Continuando con los aspectos escolares, los participantes en Trampolín mayoritariamente pertenecen a centros públicos.…”
Section: Discussionunclassified